RCGP research and surveillance centre annual report 2014-2015: disparities in presentations to primary care - De Lusignan, S; Correa, A; Pathirannehelage, S; Byford, R; Yonova, I; Elliot, AJ; Lamagni, T; Amirthalingam, G; Pebody, R; Smith, G; Jones, S; Rafi, I (Royal College of General Practitioners, 2016)
BACKGROUND: The Royal College of General Practitioners (RCGP) Research and Surveillance Centre (RSC) comprises over 100 general practices in England, with a population of around 1 million, providing a public health surveillance system for England and data for research. AIM: To demonstrate the scope of data with the RCGP Annual Report 2014-2015 (May 2014 to April 2015) by describing disparities in the presentation of six common conditions included in the report. DESIGN AND SETTING: This is a report of respiratory and communicable disease incidence from a primary care sentinel network in England. METHOD: Incidence rates and demographic profiles are described for common cold, acute otitis media, pneumonia, influenza-like illness, herpes zoster, and scarlet fever. The impact of age, sex, ethnicity, and deprivation on the diagnosis of each condition is explored using a multivariate logistic regression. RESULTS: With the exception of herpes zoster, all conditions followed a seasonal pattern. Apart from pneumonia and scarlet fever, the odds of presenting with any of the selected conditions were greater for females (P<0.001). Older people had a greater probability of a pneumonia diagnosis (≥75 years, odds ratio [OR] 6.37; P<0.001). Common cold and influenza-like illness were more likely in people from ethnic minorities than white people, while the converse was true for acute otitis media and herpes zoster. There were higher odds of acute otitis media and herpes zoster diagnosis among the less deprived (least deprived quintile, OR 1.32 and 1.48, respectively; P<0.001). CONCLUSION: The RCGP RSC database provides insight into the content and range of GP workload and provides insight into current public health concerns. Further research is needed to explore these disparities in presentation to primary care.